Pengaruh Media Sosial Terhadap Loneliness yang Dimediasi Fear Of Missing Out pada Kalangan Generasi Z di Era Digital - Hunaydah Hunaydah; Ries Wulandari (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The rapid development of digital technology has made social media an inseparable part of Generation Z’s daily life. High intensity of social media use is often associated with various psychological impacts, such as Fear of Missing Out (FOMO) and loneliness. This study aims to analyze the effect of social media use on the level of Fear of Missing Out (FOMO), identify the influence of loneliness on FOMO, and examine the direct effect of social media use on loneliness among Generation Z. In addition, this study seeks to explain the role of FOMO as a mediating variable in the relationship between social media use and loneliness in the digital era, which is increasingly influenced by technological advancements and artificial intelligence (AI). This research employs a quantitative approach using a case study method involving Generation Z individuals residing in the Bogor area and its surroundings. Data were collected through the distribution of online questionnaires to respondents who met the criteria of Generation Z age range and active social media usage. The collected data were analyzed using SmartPLS 4.0 software with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach to examine both direct and indirect relationships among the research variables. The results indicate that social media use has a positive and significant effect on Fear of Missing Out (FOMO) among Generation Z. Furthermore, loneliness is also proven to have a positive and significant effect on FOMO. However, social media use does not have a significant effect on loneliness. Additionally, FOMO does not function as a mediating variable in the relationship between social media use and loneliness. These findings suggest that FOMO is more strongly influenced by the intensity of social media use and individuals’ emotional conditions, but it does not serve as a key link between social media use and feelings of loneliness. This study is expected to provide theoretical and practical contributions to understanding the psychological dynamics of Generation Z in the digital era.